How Analysts Think: Sense-making Strategies in the Analysis of Temporal Evolution and Criminal Network Structures and Activities. (September 2017) - Haider, Johanna Doppler; Seidler, Patrick; Pohl, Margit; Kodagoda, Neesha; Adderley, Rick; Wong, B. L. William
Analysis of criminal activity based on offenders' social networks is an established procedure in intelligence analysis. The complexity of the data poses an obstacle for analysts to gauge network developments, e.g. detect emerging problems. Visualization is a powerful tool to achieve this, but it is essential to know how the analysts' sense-making strategies can be supported most efficiently. Based on a think aloud study we identified ten cognitive strategies on a general level to be useful for designers. We also provide some examples how these strategies can be supported through appropriate visualizations.